SENSITIVITY AND SPECIFICITY OF A NEW TOOL FOR EARLY DETECTION OF RISK FACTORS FOR NON COMMUNICABLE DISEASES IN URBAN WORKERS - Hildagardis Meliyani Erista Nai; Risky Wulandari (The Indonesian Journal of Public Health, 2024)
Introduction: Non communicable diseases (NCDs) have an impact on health, economy, and quality of life, and can reduce worker productivity. Approximately 41 million people die from NCDs every year, accounting for 74% of deaths worldwide. The Deteksi Dini Faktor Risiko Gizi dan Kesehatan (DDR-GizKes) is instrument designed for the early detection of nutritional and health risk factors related to NCDs that affect the productivity of urban workers . A screening test is essential part of this newly developed tool. Aims: This study aims to test the sensitivity and specificity of the DDR-GizKes instrument for detecting NCDs in urban workers. Methods: This study used a descriptive observational design with a cross-sectional approach. The population consisted of 227 teachers and staff in high schools in Yogyakarta who were selected using a cluster random sampling technique. Hypertension was used as the gold standard for the screening test. Results: The nutritional risk factor test had a sensitivity of 15.8% and a specificity of 94.2%. The positive predictive value (PPV) for the nutritional risk factor was 16.7% and the negative predictive value (NPV) was 93.8%. Meanwhile,  the health risk factor test had a sensitivity of 15.8% and a specificity of 86.4%. The PPV for the health risk factor was 7.89% and the NPV was 93.3%. Conclusion: The DDR-GizKes instrument had low sensitivity but high specificity. Further research is necessary to establish the scoring system of the DDR-GizKes instrument in populations with a high prevalence of NCDs using a larger sample size.